From disciplines to “studies” - Lucas Monteil; Alice Romerio (Revue d'anthropologie des connaissances)
The studies are debated within the academic space, with regard to the structure of disciplines. They claim an ability to produce conceptual or paradigmatic shifts. Taking epistemic and analytical issues seriously, their study also implies understanding the long term of scientific institutionalization. The historical sociology of disciplines indicates that a process of segmentation underlies the modern development of academic and scientific life. The analysis of their development argues for their reinstatement in historically changing power structures. Interdisciplinarity questions the future of the disciplinary organization of science. The emergence of studies appears to be the high point of recent transformations in the academic space.